Ytterbium-doped nano spherical CeO2 particle as well as preparation method and application thereof

Nanosphere CeO2 particles are prepared by ytterbium-doped hydrothermal method, which solves the problem of large distribution and easy agglomeration of existing cerium oxide abrasive particles, and realizes the ultra-smooth surface and efficient removal rate of optical glass.

CN119528200APending Publication Date: 2025-02-28SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411440378.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing cerium oxide nano-abrasive particles have large particle size distribution and are prone to agglomeration, resulting in mechanical damage to the surface during optical glass polishing, and it is difficult to improve the removal rate and surface quality at the same time.

Method used

Nanospherical CeO2 particles were prepared by ytterbium-doped hydrothermal method. By controlling the hydrothermal time and reaction conditions, nanospherical CeO2 particles with narrow particle size distribution and good dispersion were obtained.

Benefits of technology

The ultra-smooth surface of optical glass is achieved, reducing surface mechanical damage, and improving material removal rate and surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528200A_ABST
    Figure CN119528200A_ABST
Patent Text Reader

Abstract

The invention discloses ytterbium-doped nano spherical CeO2 particles as well as a preparation method and application thereof. The preparation method comprises the following steps: preparing a cerium source solution and an ytterbium source solution at room temperature; adding ethylene glycol into the prepared cerium source solution, uniformly mixing, adding acetic acid, fully stirring, adding the ytterbium source solution prepared in the step 1, fully stirring, transferring the mixed solution into a hydrothermal reaction kettle with polytetrafluoroethylene, carrying out a hydrothermal reaction, separating solid substances, drying, and sintering in a muffle furnace at 500-600 DEG C for 2-4 hours to obtain the ytterbium-doped cerium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium-doped ytterbium composite material. Then cooling along with the furnace to obtain ytterbium-doped nano spherical CeO2 particles; the formula is simple, the cost is low, the production process requirement is low, the prepared product is good in dispersity and narrow in size distribution, and the surface mechanical damage of the optical glass is further reduced on the basis of ensuring a certain material removal rate, so that the ultra-smooth surface of the optical glass is realized, and the surface quality is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to polishing materials, and specifically relates to ytterbium-doped nano-spherical CeO2 particles and a preparation method and application thereof. Background Art

[0002] Chemical Mechanical Polishing (CMP) is a global flattening technology that combines surface chemical action and mechanical grinding to achieve a high (nanoscale) flattening effect of materials and obtain an ultra-smooth surface. It is currently widely used in optical glass, computer hard disks, integrated circuits, semiconductors and other fields. The CMP system is mainly composed of three parts: polishing equipment, polishing pads and polishing liquid. In the CMP process, the polishing liquid is responsible for the "softening" and removal of the material surface, and is an important factor affecting the CMP performance. It is mainly composed of abrasive particles, oxidants, pH regulators, and surfactants. The abrasive particles must contact, adsorb, and rub against the workpiece surface, and are the most important part of the polishing liquid. At present, the abrasives used in CMP are mainly inorganic oxide nano-abrasive particles, including cerium oxide (CeO2), silicon oxide (SiO2), aluminum oxide (Al2O3), manganese oxide (MnO2), zirconium oxide (ZrO2) and diamond. Among them, cerium oxide has a special chemical tooth effect with silicon oxide, so it has a high polishing rate and surface quality in the polishing of silicon-based materials. Research has found that the polishing ability of cerium oxide on silicon-based materials is closely related to its morphology. Spherical abrasive particles with narrow distribution and small size can produce rolling friction to remove the oxide layer of silicon-based materials, making the silicon-based materials have better surface roughness and good material removal rate. In addition, the doping of ytterbium elements can improve the Ce of cerium oxide abrasive particles. 3+ In the preparation of existing cerium oxide nano-abrasives, the particle size distribution is large and easy to agglomerate, the effective particles are few, and the agglomerated particles have concentrated stress, which easily causes surface mechanical damage during the optical glass polishing process. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an ytterbium-doped nano-spherical CeO2 particle and a preparation method and application thereof, which have good dispersibility and narrow size distribution, and further reduce the surface mechanical damage of the optical glass on the basis of ensuring a certain material removal rate, so as to achieve an ultra-smooth surface of the optical glass and improve the surface quality.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for preparing ytterbium-doped nano-spherical CeO2 particles comprises the following steps:

[0006] Step 1: Dissolve 0.94-0.98 g Ce(NO3)3·6H2O and 0.01-0.05 g Yb(NO3)3·6H2O in 1-2 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution;

[0007] Step 2: first add 20-30 mL of ethylene glycol to the cerium source solution prepared in step 1 and mix evenly, then add 1-2 mL of acetic acid and stir thoroughly, then add the ytterbium source solution prepared in step 1 and stir thoroughly, then transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, put it in a 180°C constant temperature oven to react for 4-5 hours, then centrifuge, wash and dry;

[0008] Step 3: Transfer the dried product of step 2 to a muffle furnace and sinter it at 500-600° C. for 2-4 hours, then cool it in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0009] The present invention also has the following technical features:

[0010] Preferably, the sufficient stirring in step 2 is magnetic stirring for 10 to 15 minutes.

[0011] Preferably, the washing in step 2 is washing with distilled water and alcohol respectively 2 to 3 times.

[0012] Preferably, the drying in step 2 is to disperse the washed product in ethanol and place it in a porcelain boat, and then transfer the porcelain boat to an oven and dry it at 60-90° C. for 10-12 hours.

[0013] The present invention also protects ytterbium-doped nano-spherical CeO2 particles prepared by the method as described above, with a size of 120-155 nm.

[0014] The present invention also protects the use of the ytterbium-doped nano-spherical CeO2 particles as described above in chemical mechanical polishing.

[0015] Compared with the prior art, the present invention has the following technical effects:

[0016] The present invention uses Ce 3+ Using ytterbium as raw material and ytterbium as doping element, a precursor with spherical structure is prepared by controlling the hydrothermal time to realize uniformly distributed ytterbium-doped nano-spherical CeO2 particles with a particle size of 120nm-155nm; the formula is simple, the cost is low, and the production process requirements are low. The prepared product has good dispersibility and narrow size distribution. On the basis of ensuring a certain material removal rate, the surface mechanical damage of the optical glass is further reduced to realize an ultra-smooth surface of the optical glass and improve the surface quality;

[0017] The polishing liquid used for chemical mechanical polishing prepared by the ytterbium-doped nano-spherical CeO2 particles synthesized by the present invention is used to perform surface processing on quartz glass, and the material removal rate is 144.68nm / min, and the surface quality Ra is 0.18nm. This is because the ytterbium-doped nano-spherical CeO2 particles are spherical and have a narrow size distribution. During polishing, the sliding friction between the particles and the workpiece can be converted into rolling friction, and the local stress is small, thereby reducing surface scratches during chemical mechanical polishing. In addition, the ytterbium doping increases the concentration of trivalent cerium ions on the particle surface, and Ce 3+ As an active site during polishing, it can weaken the Si-O-Si bond and form a Ce-O-Si bond with stronger bond energy, thereby enhancing the chemical mechanical polishing ability of the particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 XRD spectrum of the cerium oxide abrasive prepared in Example 1;

[0019] Figure 2 This is a SEM image of the cerium oxide abrasive prepared in Example 2;

[0020] Figure 3 is the chemical mechanical polishing material removal rate value of the cerium oxide abrasive polishing solution prepared in Examples 1-5;

[0021] Figure 4 The surface roughness of the chemical mechanical polishing material of the cerium oxide abrasive polishing solution prepared in Example 2. DETAILED DESCRIPTION

[0022] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.

[0023] Example 1

[0024] Step 1: Dissolve 0.98 g Ce(NO3)3·6H2O and 0.01 g Yb(NO3)3·6H2O in 1 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution respectively;

[0025] Step 2: first add 26 mL of ethylene glycol to the aqueous solution of the cerium source and mix evenly, then add 1 mL of acetic acid and stir magnetically for 10 minutes, then add the aqueous solution containing the ytterbium source, stir magnetically for 10 minutes to mix thoroughly, transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, place it in a 180°C constant temperature oven and let it react for 240 minutes, wash the product with water and alcohol and centrifuge it twice, and remove the upper liquid by centrifugation; use an ultrasonic machine to evenly disperse it in a centrifuge tube before centrifugation, disperse the washed product in ethanol and place it in a porcelain boat, transfer the porcelain boat to an oven and dry it at 70°C for 10 hours;

[0026] Step 3: Transfer the dried porcelain boat to a muffle furnace, heat it from room temperature to 600°C at 5°C / min, keep it warm for 2 hours, perform calcination, and then cool it to room temperature in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0027] Figure 1 is the XRD spectrum of the cerium oxide particles synthesized in Example 1; Figure 1 As shown, no second phase peak appears, and the (111) peak has a slight shift, compared with the cerium oxide PDF card (#PDF 34-0394), indicating that ytterbium-doped CeO2 nanoparticles are successfully prepared.

[0028] Figure 2 is a SEM image of the Yb-doped CeO2 nanoparticles synthesized in Example 1; Figure 2 As shown, the particle size synthesized in Example 1 is about 138.9 nm, with a moderate size and a narrow particle size distribution.

[0029] Figure 3 The chemical mechanical polishing material removal rate of the ytterbium-doped CeO2 particle polishing solution prepared in Example 1.

[0030] Figure 4 The surface roughness of the ytterbium-doped CeO2 nanoparticle polishing liquid prepared in Example 1; Figure 4 As shown, the surface roughness of the material is low, which is due to the fact that the morphology of the particles is mainly spherical and the size distribution of the particles is narrow.

[0031] Example 2

[0032] Step 1: Dissolve 0.96 g Ce(NO3)3·6H2O and 0.03 g Yb(NO3)3·6H2O in 1 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution respectively;

[0033] Step 2: first add 26 mL of ethylene glycol to the aqueous solution of the cerium source and mix evenly, then add 1 mL of acetic acid and stir magnetically for 10 minutes, then add the aqueous solution containing the ytterbium source, stir magnetically for 10 minutes to mix thoroughly, transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, and place it in a 180°C constant temperature oven for 240 minutes; wash the product with water and alcohol and centrifuge it three times respectively, and remove the upper liquid by centrifugation; use an ultrasonic machine to evenly disperse it in a centrifuge tube before centrifugation; disperse the washed product in ethanol and place it in a porcelain boat, transfer the porcelain boat to an oven and dry it at 70°C for 10 hours;

[0034] Step 3: Transfer the dried porcelain boat to a muffle furnace, heat it from room temperature to 600°C at 5°C / min, keep it warm for 2 hours, perform calcination, and then cool it to room temperature in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0035] Example 3

[0036] Step 1: Dissolve 0.94 g Ce(NO3)3·6H2O and 0.05 g Yb(NO3)3·6H2O in 1 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution respectively;

[0037] Step 2: first add 26 mL of ethylene glycol to the aqueous solution of the cerium source and mix evenly, then add 1 mL of acetic acid and stir magnetically for 10 minutes, then add the aqueous solution containing the ytterbium source, and stir magnetically for 10 minutes to mix thoroughly; transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, and place it in a 180°C constant temperature oven for 300 minutes; wash the product with water and alcohol and centrifuge it twice, and remove the upper liquid by centrifugation; use an ultrasonic machine to evenly disperse it in a centrifuge tube before centrifugation; disperse the washed product in ethanol and place it in a porcelain boat, and transfer the porcelain boat to an oven and dry it at 60°C for 12 hours;

[0038] Step 3: Transfer the dried porcelain boat obtained in step 2 to a muffle furnace and heat it from room temperature to 600°C at a rate of 5°C / min, keep it at that temperature for 2 hours, perform calcination, and then cool it to room temperature in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0039] Example 4

[0040] Step 1: Dissolve 0.98 g Ce(NO3)3·6H2O and 0.01 g Yb(NO3)3·6H2O in 2 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution respectively;

[0041] Step 2: first add 30 mL of ethylene glycol to the aqueous solution of the cerium source and mix evenly, then add 1.5 mL of acetic acid and stir magnetically for 12 minutes, then add the aqueous solution containing the ytterbium source and stir magnetically for 12 minutes to mix thoroughly; transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, and place it in a 180°C constant temperature oven for 270 minutes; wash the product with water and alcohol and centrifuge it twice, and remove the upper liquid by centrifugation; use an ultrasonic machine to evenly disperse it in a centrifuge tube before centrifugation; disperse the washed product in ethanol and place it in a porcelain boat, transfer the porcelain boat to an oven and dry it at 90°C for 10 hours;

[0042] Step 3: Transfer the dried porcelain boat to a muffle furnace, heat it from room temperature to 500°C at 5°C / min, keep it warm for 4 hours, perform calcination, and then cool it to room temperature in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0043] Example 5

[0044] Step 1: Dissolve 0.98 g Ce(NO3)3·6H2O and 0.01 g Yb(NO3)3·6H2O in 1.5 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution;

[0045] Step 2: first add 20 mL of ethylene glycol to the aqueous solution of the cerium source and mix evenly, then add 2 mL of acetic acid and stir magnetically for 15 minutes, then add the aqueous solution containing the ytterbium source and stir magnetically for 15 minutes to mix thoroughly; transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, and place it in a 180°C constant temperature oven for 240 minutes; wash the product with water and alcohol and centrifuge it twice, and remove the upper liquid by centrifugation; use an ultrasonic machine to evenly disperse it in a centrifuge tube before centrifugation; disperse the washed product in ethanol and place it in a porcelain boat, transfer the porcelain boat to an oven and dry it at 80°C for 11 hours;

[0046] Step 3: Transfer the dried porcelain boat to a muffle furnace, heat it from room temperature to 550°C at 5°C / min, keep it warm for 3 hours, perform calcination, and then cool it to room temperature in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0047] Example 6

[0048] Step 1: Dissolve 0.96 g Ce(NO3)3·6H2O and 0.03 g Yb(NO3)3·6H2O in 1 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution respectively;

[0049] Step 2: first add 26 mL of ethylene glycol to the aqueous solution of the cerium source and mix evenly, then add 1 mL of acetic acid and stir thoroughly, then add the aqueous solution containing the ytterbium source, and stir thoroughly for 10 minutes using a magnetic stirrer; transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, and place it in a 180°C constant temperature oven for 270 minutes; wash the product with water and alcohol and centrifuge it twice, and remove the upper liquid by centrifugation; use an ultrasonic machine to evenly disperse it in a centrifuge tube before centrifugation; disperse the washed product in ethanol and place it in a porcelain boat, and transfer the porcelain boat to an oven and dry it at 70°C for 10 hours;

[0050] Step 3: Transfer the dried porcelain boat obtained in step 2 to a muffle furnace and heat it from room temperature to 600°C at a rate of 5°C / min, keep it at that temperature for 4 hours, perform calcination, and then cool it to room temperature in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

[0051] The above specific embodiments are only selected examples to clearly illustrate the effects that can be achieved by the present invention, and cannot be simply considered as all implementation schemes of the present invention. For practitioners in the relevant field, other changes can be made on the basis of the above scheme description, which cannot be exhaustively listed here. Any changes in numerical values ​​derived from the design principles of the present invention still fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing ytterbium-doped nano-spherical CeO2 particles, characterized in that: The following steps are involved: Step 1: Dissolve 0.94-0.98 g Ce(NO3)3·6H2O and 0.01-0.05 g Yb(NO3)3·6H2O in 1-2 mL deionized water at room temperature to form a cerium source solution and a ytterbium source solution; Step 2: first add 20-30 mL of ethylene glycol to the cerium source solution prepared in step 1 and mix evenly, then add 1-2 mL of acetic acid and stir thoroughly, then add the ytterbium source solution prepared in step 1 and stir thoroughly, then transfer the mixed solution into a hydrothermal reactor with polytetrafluoroethylene, tighten the seal, put it in a 180°C constant temperature oven to react for 4-5 hours, then centrifuge, wash and dry; Step 3: Transfer the dried product of step 2 to a muffle furnace and sinter it at 500-600° C. for 2-4 hours, then cool it in the furnace to obtain ytterbium-doped nano-spherical CeO2 particles.

2. The method for preparing ytterbium-doped nano-spherical CeO2 particles according to claim 1, characterized in that: The sufficient stirring described in step 2 is magnetic stirring for 10 to 15 minutes.

3. The method for preparing ytterbium-doped nano-spherical CeO2 particles according to claim 1, characterized in that: The washing described in step 2 is washing with distilled water and alcohol respectively 2 to 3 times.

4. The method for preparing ytterbium-doped nano-spherical CeO2 particles according to claim 1, characterized in that: The drying in step 2 is to disperse the washed product in ethanol and place it in a porcelain boat, and then transfer the porcelain boat to an oven and dry it at 60-90° C. for 10-12 hours.

5. A nano-spherical CeO2 particle doped with ytterbium prepared by the method according to any one of claims 1 to 4, characterized in that: The size is 120~155nm.

6. Use of the ytterbium-doped nano-spherical CeO2 particles as claimed in claim 5 in chemical mechanical polishing.